ANALISIS PENGGUNAAN KOMIK SEBAGAI MEDIA PEMBELAJARAN DALAM EVALUASI PEMBELAJARAN SEJARAH UNTUK MENINGKATKAN KREATIVITAS PESERTA DIDIK FASE E - Tomy Wijaya; Fatimah Alauwiyah; Muhammad Reza Pahlevi (SUKMA: Jurnal Pendidikan, 2025)
The problem raised in this article is the lack of creativity of students in learning history in phase E. The purpose of this research is to find out the analysis of the use of comics as a teaching aid in evaluating history learning to improve students' creativity. The paradigm that develops in learning history is that it tends to be memorized and less varied. The research applied by the author uses descriptive qualitative research methods. The approach used is observation in the form of taking a questionnaire addressed to students in phase E as many as 20 students. phase E and the questionnaire consists of 10 questions. The results of the study concluded that the use of comic media is an important aspect to support learning and increase students' creativity in learning history phase E.